Moral Values in Indonesian Textbooks for First Grade: A Multimodality Discourse Analysis - Wisna Rahmayanti; Fahmi Gunawan; Karim Karim; Sitti Fauziah; Raehang Raehang (CV Projurnal Mitra Publikasi, 2025)
The increasing concern over moral degradation among elementary school children underscores the urgent need to examine how educational materials can serve as a medium for character formation. This study investigates the moral values embedded in the Indonesian language textbook Bahasa Indonesia: Aku Bisa! for first-grade students (2023 revised edition) and examines how these values are represented through a multimodal discourse analysis approach. A qualitative descriptive design was employed, applying multimodal discourse analysis grounded in Moral Foundations Theory and the national Character Education Reinforcement framework. The research object was the entire textbook, which comprises eight thematic chapters. Data were collected by systematically identifying and documenting all verbal and visual elements within the book, including written texts, illustrations, symbols, and interactive learning activities. The findings indicate that moral values such as care, fairness, loyalty, respect for authority, and sanctity are presented contextually and integratively throughout the textbook. These align with core character education principles including religiosity, nationalism, independence, cooperation, and integrity. Narrative structures, visual representations, and participatory tasks work together to foster a holistic moral understanding among young learners. Overall, the textbook not only facilitates foundational literacy development but also plays a strategic role in character formation aligned with the Pancasila Student Profile. The study highlights the importance of incorporating multimodal design in textbook development as an effective approach to strengthening character education.